Benjamin C. Jantzen, An Introduction to Design Arguments - Branch, Glenn (Journal for the Study of Religion, Nature and Culture, 2018)
Benjamin C. Jantzen, An Introduction to Design Arguments (Cambridge: Cambridge University Press, 2014), 347pp., 29.95 (pbk), ISBN: 978-0-52-118303-1.